Relationship between serum carotenoids and telomere length in overweight or obese individuals - Wang, Jiang; Xie, Fayi; Zhu, Wan; Ye, Dongmei; Xiao, Yi; Shi, Mengxia; Zeng, Rui; Bian, Jiahui; Xu, Xiao; Chen, Lihuan; Zhu, Aizhang; Zhu, Ke; et al. (Frontiers in Nutrition, 2024)
Background Previous researches have demonstrated an association between carotenoids and elongated telomeres. Nonetheless, there is scant scientific evidence examining this relationship in individuals who are overweight or obese, a demographic more predisposed to accelerated aging. This study aims to elucidate the correlation between serum carotenoid concentrations and telomere length within this population group. Methods Data were sourced from the 2001–2002 National Health and Nutrition Examination Survey, encompassing 2,353 overweight or obese participants. The levels of α-carotene, β-carotene (both trans and cis isomers), β-cryptoxanthin, lutein/zeaxanthin, and trans-lycopene were quantified via high-performance liquid chromatography. Telomere length was assessed using quantitative polymerase chain reaction. Results Following adjustment for potential confounders, telomere length exhibited an increase of 1.83 base pairs (bp) per unit elevation in β-carotene levels (β = 1.83; 95% CI: 0.48, 3.18). Within the fully adjusted model, telomere length incremented by 1.7 bp per unit increase in serum β-carotene among overweight individuals (β = 1.7; 95% CI: 0.1, 3.3), and by 2.6 bp per unit increase among obese individuals (β = 2.6; 95% CI: 0.1, 5.0). Furthermore, restricted cubic spline analysis revealed a linear relationship between β-carotene levels and telomere length, whereas a non-linear association was observed between β-cryptoxanthin levels and telomere length. Conclusion This investigation indicates that higher serum β-carotene concentrations are linked with extended telomere length in overweight and obese populations in the United States. These findings warrant further validation through prospective studies.